Pembangunan Sistem Monitoring Data Kualitas Udara Berbasis Iot Di Universitas Riau - Middinali, Nadjum; Rahayu, Yusnita (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2019)
Air Quality is very important for life. Air monitoring is very necessary to anticipate the dangerous air pollution. Excellent air monitoring done in real time, so that the monitoring data obtained directly. In the research make aplication air monitoring real time device using internet of thing in waspmote plug and sense for monitoring of PM10 and waspmote OEM for monitoring CO and O3, data communication using Zigbee. Application Microsoft Visual Basic 2010 used as processing and connection to database MySQL. Design database air monitoring to connect monitoring so data can be stored. Application will process waspmote data to ISPU data for reference condition the air content PM10, CO dan O3, will display ISPU in Website. The research also compares the result of sensor monitoring with AQMS in BLH and BMKG Pekanbaru. Keywords : Internet of Thing, Zigbee, Database, Real time, Air polution, Website